The Influence of Competency, Auditor Independence, Objectivity on Audit Quality with Auditor Ethics as a Moderation Variable - Insani, Yayang Nur; Suryadi, Nanda (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
The purpose of this research is to test hypotheses and produce evidence regarding the influence of Competence, Auditor Independence, Objectivity on Audit Quality with Auditor Ethics as a Moderating Variable for Studies in Pekanbaru City KAP. This research uses primary data, namely distributing questionnaires to all auditors in KAP Pekanbaru city, Competence, Auditor Independence, Objectivity. The sampling used in this research was the purposive sampling method. The number of auditors sampled in this study was 77 respondents. The analytical method used to test the hypothesis is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the SmartPLS 4.0 analysis tool. The results of this research show that Objectivity on audit quality has a positive effect and auditor independence moderates auditor ethics and has a positive and significant effect on audit quality, but Competence and Independence have a negative and insignificant effect on audit quality.